Calicnemia fortis sp. nov. from Pakistan (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A.; Zia, Ahmed; Naeem, Muhammad; Rafi, Muhammad Ather (Zootaxa, 2014)
Calicnemia fortis sp. nov. is described from Azad Jammu and Kashmir in Pakistan and compared with other group 2 species of Calicnemia.